2017
DOI: 10.1098/rsos.170748
|View full text |Cite
|
Sign up to set email alerts
|

Fe(OTf) 3 -catalysed Friedel–Crafts reaction of benzenoid arenes with α,β-unsaturated carbonyl compounds: easy access to 1,1-diarylalkanes

Abstract: A simple and efficient method for the synthesis of 1,1-diarylalkanes via the Friedel–Crafts-type alkylation reaction of electron-rich arenes with cinnamic acid ester derivatives or chalcones is reported. Iron triflate has been found to be the best catalyst for the Friedel–Crafts-type alkylation reaction with α,β-unsaturated carbonyl compounds. This reaction afforded β,β-diaryl carbonyl compounds in good yields (65–93%) and with excellent regioselectivities. Remarkably, this method is also compatible with a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Therefore, the replacement of liquid acid catalysts in Friedel-Crafts reactions with heterogeneous catalysts is a promising strategy in green chemistry. Many types of solid catalysts have been studied such as Sb supporting K10 [1], Si-MCM-41-supported Ga 2 O 3 and In 2 O 3 [2], solid super acids based on sul-fated ZrO 2 [3], Fe (OTf) 3 [4], zinc-modified MCM-22 [5], FeCl 3 , MnCl 2 , CoCl 2 , NiCl 2 , CuCl 2 , ZnCl 2 supported on acidic alumina [6], Hf/SBA-15 [7], K 2 FeZrP 3 O 12 [8], FeY zeolite [9], mesoporous AlSBA-15 [10], ZSM-5 zeolites [11], silica-immobilized FeCl 3 [12], H-Beta zeolite [13], mesoporous mordenite [14], niobium-containing zeolites [15], and ion-exchanged clays [16]. Cseri et al [16] showed that the mechanism of benzylation of benzene with benzyl chloride on solid catalysts differs from the classical acid mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the replacement of liquid acid catalysts in Friedel-Crafts reactions with heterogeneous catalysts is a promising strategy in green chemistry. Many types of solid catalysts have been studied such as Sb supporting K10 [1], Si-MCM-41-supported Ga 2 O 3 and In 2 O 3 [2], solid super acids based on sul-fated ZrO 2 [3], Fe (OTf) 3 [4], zinc-modified MCM-22 [5], FeCl 3 , MnCl 2 , CoCl 2 , NiCl 2 , CuCl 2 , ZnCl 2 supported on acidic alumina [6], Hf/SBA-15 [7], K 2 FeZrP 3 O 12 [8], FeY zeolite [9], mesoporous AlSBA-15 [10], ZSM-5 zeolites [11], silica-immobilized FeCl 3 [12], H-Beta zeolite [13], mesoporous mordenite [14], niobium-containing zeolites [15], and ion-exchanged clays [16]. Cseri et al [16] showed that the mechanism of benzylation of benzene with benzyl chloride on solid catalysts differs from the classical acid mechanism.…”
Section: Introductionmentioning
confidence: 99%